Linking Irrigation with Development The Kerala Experience - D Narayana K Narayanan Nair (ECONOMIC AND POLITICAL WEEKLY, 1983)
Disproportionately high investment in irrigation in Kerala has nevertheless been marked by long time overruns in completion of projects and a far lower area than that targetted being brought under irrigation. The bulk of the investment, moreover, is for major-medium projects, and is intended for paddy lands. This paper aims in Section I to consider to what extent irrigation has succeeded in increasing and stabilising paddy yields; and in Section II to explore the possible reasons hindering proper use of irrigation water in paddy cultivation.